2005
DOI: 10.1063/1.2128064
|View full text |Cite
|
Sign up to set email alerts
|

p type doping of zinc oxide by arsenic ion implantation

Abstract: Braunstein, G.; Muraviev, A.; Saxena, H.; Dhere, N.; Richter, V.; and Kalish, R., "p type doping of zinc oxide by arsenic ion implantation" (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 27 publications
(18 reference statements)
1
41
0
Order By: Relevance
“…This issue is of particular relevance, since it has been reported that not more than 5-13% of incorporated As can be electrically activated in ZnO [4,5,7]. The maximum concentration of As in our implanted sample (around 7.6×10 18 cm −3 ) is comparable with the As concentration used in most other studies.…”
Section: Relevance Of Current Results With Respect To the Acceptor Mosupporting
confidence: 70%
See 1 more Smart Citation
“…This issue is of particular relevance, since it has been reported that not more than 5-13% of incorporated As can be electrically activated in ZnO [4,5,7]. The maximum concentration of As in our implanted sample (around 7.6×10 18 cm −3 ) is comparable with the As concentration used in most other studies.…”
Section: Relevance Of Current Results With Respect To the Acceptor Mosupporting
confidence: 70%
“…In the case of the technologically promising II-VI compound ZnO, besides N [1,2] the heavy group-V elements P [1,2], As [2][3][4][5][6][7][8][9], and Sb [10][11][12] have been reported in the literature as possible p-type dopants. However, there is an ongoing debate whether for P, As, and Sb the p-type character results from these impuritities simply replacing O atoms, thus acting as simple "chemical" dopants [3,4,8], or is due to the formation of more complicated defect complexes [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This issue is of particular relevance, since it has for instance been reported that not more than 5-13% of incorporated As can be electrically activated in ZnO 13,15,16 . The maximum concentration of As in our implanted sample (≈ 8×10…”
Section: Relevance Of Current Results With Respect To the Acceptor Momentioning
confidence: 99%
“…Also based on DFT results, the experimentally observed ptype behaviour was attributed to the formation of electrically active acceptor complexes of the type P Zn −2V Zn , As Zn −2V Zn or Sb Zn −2V Zn, first predicted by Limpijumnong et al [44][45][46][47] for As and Sb and later by Shen et al 12 for P, the "complex acceptor model". While this concept is finding more and more acceptance 6,16,18,25,28,32,36,[38][39][40][41][42] , it is strongly disputed by others who support the point of view that P, As or Sb in ZnO act as simple chemical acceptors that replace oxygen 10,11,26,29,48 , the "chemical acceptor model". [52][53] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation